(untitled) (Journal of Parents and Teachers, 2026)
Fear, along with pain, is one of the first negative impressions a newborn experiences. All kinds of stimuli begin when they come into contact with the outside world. This accumulation of impressions contrasts with foetal life and generates insecurities and fears. Babies experience initial fears (perinatal and postnatal), which is why they cry when faced with the unknown: noises, people, places, etc. The development of fears has a lot to do with the influences of the environment in which the child develops, i.e. they are related to the family setting. There are variables that enhance them and also strategies to help the child at this stage of development.